HERPES VIRUS CONTAMINATION OF DONOR’S TISSUE AS A POTENTIAL ETIOLOGY OF CORNEAL GRAFT DISEASE AFTER PENETRATING KERATOPLASTY - E. A. Mironkova; P. V. Makarov; O. S. Slepova; R. A. Gundorova; A. E. Kugusheva; V. V. Demkin; T. S. Sadokhina (Вестник трансплантологии и искусственных органов)
We present the study of outcomes of PCR-diagnostics directed on detection of DNA of herpes-family viruses in donor’s corneal tissues taken during penetrating keratoplasty (PK). In total, there were 46 patients, who under- went PKs. They were followed up from 14 days till 12 months. PCR-research of fragments of a donor cornea re- vealed existence of DNA in 21.7%. The retrospective analysis showed that in the presence of herpes-virus DNA in donor’s cornea is the risk factor of postoperative complications development and increases the rejection rate 2–3 times, reaching 100% – 70%. Thus the high risk of graft failures remains associated not only with the system immunosupressive therapy which is usually considered as the precondition of activization of chronic infections, but also in the absence of that. It gives the ground to conclude that preoperative preparation of a donor material, especially «fresh» corneas, should include expanded PCR-diagnostics on herpes-viruses and its obligatory dis- carding in cases of positive tests.